Comparative Analysis of Oil Content in Dura and Tenera Palm Fruit Varieties - Shaari, Mohd Amirulhakim; Shahidan, Syazwan; Mohd Arbain, Sari Indra Saputra; Ruslan, Noraini; Hasli , Mohamad Asyraf; Mohd Fadzli, Nadia (Journal of Sustainable Natural Resources, 2023)
The oil palm (Elaeis guineensis Jacq.) is a vital crop in global agriculture, known for its high oil production. Among the oil palm varieties, Dura and Tenera stand out as the most prominent fruit types. Despite the economic significance of the oil palm, there has been limited research aimed at thoroughly examining the components of oil content between Dura and Tenera fruits. It is crucial to comprehend how these fruit types affect oil content, particularly in terms of the percentage of oil to bunch (OTB%), percentage of oil to fruit (OTF%), and percentage of oil to dry mesocarp (%OTDM), as this knowledge is crucial in determining the quality of oil palm cultivation and ensuring sustainable oil production. This study seeks to bridge the existing knowledge gap by investigating the influence of different fruit types, Dura and Tenera, on %OTF, %OTB, and %OTDM. We have gathered a dataset of %OTF, %OTB, and %OTDM from oil palm plantations representing both Dura and Tenera fruit types. Our analysis reveals substantial differences in the percentages of %OTF, %OTB, and %OTDM between Dura and Tenera oil palm fruit types. Particularly noteworthy is the significant variation in the oil-to-fruit percentage, underscoring a marked distinction between Tenera and Dura palms, characterized by a p-value of 0.00 and a robust t-value of 11.56 by using the statistical examination. This finding aligns with the industry’s perception of Tenera as a superior cultivar for oil yield, supported by its significantly higher oil accumulation within individual fruits.